Spatio-temporal dynamics and drivers of highly pathogenic avian influenza H5N1 in Chile - Azat, Claudio; Alvarado-Rybak, Mario; Aguilera, José F.; Benavides, Julio A. (Frontiers in Veterinary Science, 2024)
Highly pathogenic avian influenza A H5N1 clade 2.3.4.4b (hereafter H5N1) is causing vast impacts on biodiversity and poultry around the globe. In Chile, lethal H5N1 cases have been reported in a wide range of wild bird species, marine mammals, backyard and industrial poultry, and in a human. This study describes the spatio-temporal patterns of the current epizootic of H5N1 in Chile and test drivers that could be associated with outbreak occurrence. We used H5N1 cases reported by the Chilean national animal health authority from December 5 th , 2022, to April 5 th , 2023. These included wild bird cases confirmed through avian influenza specific real-time reverse transcription PCR assay (RT-qPCR), obtained from passive and active surveillance. Data was analyzed to detect the presence of H5N1 clusters under space-time permutation probability modelling, H5N1 association between distance and days since first outbreak through linear regression, and correlation between H5N1 presence and a range of ecological and anthropogenic variables by general linear modelling. From 445 H5N1 identified outbreaks, involving 613 individual cases in wild birds, a consistent wave-like spread of H5N1 from north to south was identified, that can help predict hotspots of outbreak risk. For instance, seven statistically significant clusters were identified in central and northern Chile, where poultry production and wildlife mortalities are concentrated, respectively. The presence of outbreaks was correlated with landscape-scale variables, notably temperature range, bird richness and human footprint. In less than a year H5N1 has been associated with the unusual mortality of >100,000 individuals of wild animals in Chile, mainly coastal birds and marine mammals. It is urgent that scientists, the poultry sector, local communities, and national health authorities co-design and implement science-based measures from a One Health perspective to avoid further H5N1 spillover from wildlife to domestic animals and humans, including rapid removal and proper disposal of wild dead animals, and the closure of public areas (e.g., beaches) reporting high wildlife mortalities.